1977
DOI: 10.1152/ajpheart.1977.232.6.h617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex hormones on blood pressure and vascular connective tissue in castrated and noncastrated male rats

Abstract: Aortic collagen and elastin were quantitated in three groups of castrated and two groups of noncastrated male rats treated by intramuscular injection for 3 wk with oil, testosterone, or estradiol. The greatest differences were found between the castrated rats receiving testosterone and those receiving estradiol, the estradiol-treated rats having significantly lower total collagen, percent collagen, total elastin, and collagen/elastin (C/E), and higher percent elastin than those rats receiving testosterone. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 0 publications
5
73
2
1
Order By: Relevance
“…The rapid time course of the reduction in arterial compliance after cessation of hormone replacement therapy and of the increase in compliance after reinstituting hormone treatment is more consistent with a vasodilator mechanism than with structural remodelling of the vessel wall, which would be expected to be a more lengthy process. 45 These findings are consistent with the transient nature (ie therapy must be continuous for benefit to be maintained) of the vasoprotective effects of postmenopausal hormone replacement therapy. 46 A more recent study evaluated systemic arterial compliance in 109 postmenopausal women receiving hormone replacement therapy compared with 108 age-matched untreated controls.…”
Section: Postmenopausal Hormone Replacement Therapy and Vascular Compsupporting
confidence: 71%
“…The rapid time course of the reduction in arterial compliance after cessation of hormone replacement therapy and of the increase in compliance after reinstituting hormone treatment is more consistent with a vasodilator mechanism than with structural remodelling of the vessel wall, which would be expected to be a more lengthy process. 45 These findings are consistent with the transient nature (ie therapy must be continuous for benefit to be maintained) of the vasoprotective effects of postmenopausal hormone replacement therapy. 46 A more recent study evaluated systemic arterial compliance in 109 postmenopausal women receiving hormone replacement therapy compared with 108 age-matched untreated controls.…”
Section: Postmenopausal Hormone Replacement Therapy and Vascular Compsupporting
confidence: 71%
“…28,29 In peri-and postmenopausal women, [30][31][32] they widen the smaller resistance vessels 33 by mechanisms that include the protection of endothelial function, 31 the potentiation of nitric oxide release 30,32 and the modulation of sympathetic reactivity. 24,34 Oestrogens may also influence the viscoelastic properties of the arterial wall by changing the relative proportions of collagen and elastin, 35 by inhibition of smooth muscle cell proliferation, or by the prevention of atherosclerotic stiffening. 36 Menopause does not occur as a sudden event but as a continuous transition from a regular menstrual cycle to ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the sample had been stratified by sex and age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), у60 years), in an attempt to recruit the same number of subjects in each stratum. Households were identified from population registries as persons who shared the same address.…”
Section: Study Populationmentioning
confidence: 99%
“…In 1970s, before the AAA experimental models, Fischer et al 56 found that rats receiving estradiol had a higher aortic elastin/collagen ratio than those receiving testosterone. More recently, sex differences in AAA have been studied in different animal models, which include the intraluminal infusion of elastase in rats 57 or mice, 58 angiotensin II (AngII) infusion in mice deficient in apolipoprotein E (Apoe À/À ), 59 and direct application of elastase at the anterior wall of the abdominal aorta in mice (Table III).…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 99%